New strategies for treatment of COVID-19 and evolution of SARS-CoV-2 according to biodiversity and evolution theory. Issue 1 (1st January 2020) - Hassab Elnabi, Sobhy E.
ABSTRACT: To treat the COVID 19, it is assumed two strategies, the first of which is design a complementary micro-RNA for 3 UTR region of virus that will be bind with it.  This might prevent the translation of virus RNA on the host ribosomes or lead to virus degradation and elimination. As for the second strategy, elevation of hydrogen ion concentration upward to alkaline pH to prevent the glycoprotein of virus envelop from binding to the host's receptor, thereby preventing the virus from entering the cells. Also we predict further development of the virus through the transmission of genetic materials and micro RNA between viruses each other or between viruses and bacteria or viruses and its hosts when they are together and have intimate contact in a living cell. There are future fears of this development and its transformation of SARS-CoV-2 into retroviruses and transfer to cDNA by reverse transcriptase (RT) and integrates into the human genome. This will explain the presence of the virus in infected people after recovery. This article also explained how SARS-CoV-2 develops. This review might help in finding potential strategies for treatment COVID-19 and help explain the development of SARS-CoV-2.